2022
DOI: 10.1116/6.0002115
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of α-Ga2O3 on sapphire and nanocrystalline β-Ga2O3 on diamond substrates by halide vapor phase epitaxy

Abstract: Halide vapor phase epitaxial (HVPE) Ga2O3 films were grown on c-plane sapphire and diamond substrates at temperatures up to 550 °C without the use of a barrier dielectric layer to protect the diamond surface. Corundum phase α-Ga2O3 was grown on the sapphire substrates, whereas the growth on diamond resulted in regions of nanocrystalline β-Ga2O3 (nc-β-Ga2O3) when oxygen was present in the HVPE reactor only during film growth. X-ray diffraction confirmed the growth of α-Ga2O3 on sapphire but failed to detect any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Hence to eliminate a set of grains, reduce defects and to promote larger grain size, an offcut along [110] diamond can be employed, as well as alternative seed layers. We note due to the lattice mismatch and high surface energy difference previous attempts to grow Ga2O3 on diamond substrates using HVPE resulted in amorphous and nano-crystalline Ga2O3 films [8,9]. To reduce lattice mismatch in our case, an (AlxGa1-x)2O3 seeding/buffer layer was used; this significantly increased the grain size of the deposited thin film.…”
Section: Ga2o3 Growth Onto Diamondmentioning
confidence: 99%
“…Hence to eliminate a set of grains, reduce defects and to promote larger grain size, an offcut along [110] diamond can be employed, as well as alternative seed layers. We note due to the lattice mismatch and high surface energy difference previous attempts to grow Ga2O3 on diamond substrates using HVPE resulted in amorphous and nano-crystalline Ga2O3 films [8,9]. To reduce lattice mismatch in our case, an (AlxGa1-x)2O3 seeding/buffer layer was used; this significantly increased the grain size of the deposited thin film.…”
Section: Ga2o3 Growth Onto Diamondmentioning
confidence: 99%
“…This can be circumvented by epitaxially growing Ga2O3 directly on the diamond, or diamond onto Ga2O3. Modak et al have reported halide vapor phase epitaxy (HVPE) of Ga2O3 on diamond substrates at a growth temperature of 550 o C to prevent oxidation of the diamond substrate; this resulted in nanocrystalline beta polymorph of Ga2O3 [12]. High temperature, low pressure chemical vapor deposition (LP-CVD) of Ga2O3 has also been reported, where the epitaxy was attempted using a low temperature seeding layer grown at 750 o C to prevent diamond oxidation, followed by a higher temperature layer growth at 920 o C to achieve the best layer quality [13].…”
Section: Mocvd Growth Of Gallium Oxide On Diamondmentioning
confidence: 99%
“…Recently, Low-Pressure Chemical Vapor Deposition (LPCVD) growth of continuous β-Ga 2 O 3 films on diamond has been demonstrated; this showed the Ga 2 O 3 layers were in (−201) orientation but provided no insight of the microstructure . Halide vapor phase epitaxially (HVPE) grown Ga 2 O 3 reported deposition on diamond, suggesting nucleation is not trivial . Knowledge of heteroepitaxial growth on diamond is not mature compared to growth on sapphire, and a detailed epitaxial study is required.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Halide vapor phase epitaxially (HVPE) grown Ga 2 O 3 reported deposition on diamond, suggesting nucleation is not trivial. 5 Knowledge of heteroepitaxial growth on diamond is not mature compared to growth on sapphire, 6 and a detailed epitaxial study is required. In this work, industry preferred MOCVD is used to grow phase dominant β-Ga 2 O 3 on (001) diamond, showing epitaxial growth of (−201) β-Ga 2 O 3 consisting of a number of different crystallographically related orientations (termed variants henceforth).…”
Section: Introductionmentioning
confidence: 99%